PENINGKATAN KEMAMPUAN MENULIS MELALUI STRATEGI SELF REGULATED LEARNING BERBANTUAN MODUL BERBASIS ROLE AUDIENCE FORMAT TOPIC DI KELAS II SDN KAUMAN I - Santika, Anas; Thohir, M Anas; Fithriyanasari, Elly (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The application of the SRL (Self-Regulated Learning) strategy and the “RAFT” (Role, Audience, Format, Topic) based module in this study aims to improve the writing skills of second-grade elementary school students in the Indonesian language subject, particularly in writing narrative texts on the theme of environmental awareness. The background of this study is the students’ low writing skills, as evidenced by their inability to formulate concepts into clear, coherent, and meaningful sentences. The Classroom Action Research method, conducted in two cycles, was used in this study. The research subjects consisted of 29 second-grade elementary school students. Assessment of writing proficiency and monitoring of student activities during the learning process served as the two data collection methods. The results showed a significant improvement. The learning achievement rate increased to 93.10% with an average score of 90 in Cycle II, up from 20.69% with an average score of 67 in Cycle I. Based on these findings, it can be concluded that the implementation of the Self-Regulated Learning (SRL) strategy in conjunction with the RAFT-based module can improve students’ writing skills and promote more focused, active, and meaningful learning by helping students develop structured story ideas with confidence.